Humanistyka performatywna - Krajewska, Anna (Przestrzenie Teorii, 2019)
This article foregrounds the collapse of the binary opposition between drama and theatre that in literary and theatre discourses are traditionally recognized as wholly separate art forms, with the former based on words and the latter based on live performances. The present author argues that by applying a performative perspective on art in its varied forms and introducing the category of the entanglement of matter and meaning, derived from quantum physics, a non-antagonistic approach to drama and theatre is still possible. The argument that sees literature as a performative art, adopted by the author, provides additional support. This article shows how changes in the very notion of the text as well as in the ontological status of literature itself have had their effect on the transformations of beliefs and conceptions grounded in the vision of the humanities understood as “the textual world” to produce the concept of “entangled world” instead. This being the case, the author proposes to depart from the concept of “text” (no matter how restructured or redefined), abandon thinking in categories of network structures (even Latour’s actor-network’s theory), and discard dialectical or holistic approaches (even the theory of cognitive blending – “cognitive amalgams”) in favour of emergent “entanglement acts”, anamorphic perspective in art reception and synaesthetic discourses. By studying experiences related to performativity in the arts and discourses related to performance studies, the article goes to show the changes currently going on in the humanities and transforming them into the perfomative humanities in the process.